FBS/BSA media concentration determines CCCP's ability to depolarize mitochondria and activate PINK1-PRKN mitophagy. Issue 11 (2nd November 2019) - Soutar, Marc P. M.; Kempthorne, Liam; Annuario, Emily; Luft, Christin; Wray, Selina; Ketteler, Robin; Ludtmann, Marthe H. R.; Plun-Favreau, Hélène
ABSTRACT: Mitochondrial quality control is essential for maintaining a healthy population of mitochondria. Two proteins associated with Parkinson disease, the kinase PINK1 and the E3 ubiquitin ligase PRKN, play a central role in the selective degradation of heavily damaged mitochondria (mitophagy), thus avoiding their toxic accumulation. Most of the knowledge on PINK1-PRKN mitophagy comes from in vitro experiments involving the treatment of mammalian cells with high concentrations of mitochondrial uncouplers, such as CCCP. These chemicals have been shown to mediate off target effects, other than mitochondrial depolarization. A matter of controversy between mitochondrial physiologists and cell biologists is the discrepancy between concentrations of CCCP needed to activate mitophagy (usually >10 μM), when compared to the much lower concentrations used to depolarize mitochondria (<1 μM). Thus, there is an urgent need for optimizing the current methods to assess PINK1-PRKN mitophagy in vitro . In this study, we address the utilization of high CCCP concentrations commonly used to activate mitophagy. Combining live fluorescence microscopy and biochemistry, we show that the FBS/BSA in the cell culture medium reduces the ability of CCCP to induce PINK1 accumulation at depolarized mitochondria, subsequent PRKN recruitment and ubiquitin phosphorylation, and ultimately mitochondrial clearance. As a result, high concentrations of CCCP are required to induce mitophagy in FBS/BSA containing media. These data unite mitochondrial physiology and mitophagy studies and are a first step toward a consensus on optimal experimental conditions for PINK1-PRKN mitophagy and mitochondrial physiology investigations to be carried out in parallel. Abbreviations: BSA: bovine serum albumin; CCCP: carbonyl cyanide m-chlorophenylhydrazone; DMEM: dulbecco's Modified Eagle's Medium; DNP: 2, 4-dinitrophenol; FBS: fetal bovine serum; FCCP: carbonyl cyanide-4-(trifluoromethoxy)phenylhydrazone; GSH: glutathione; HBSS: Hanks' balanced salt solution; mtKeima: mitochondria-targeted monomeric keima-red; PBS: phosphate buffered saline; PD: Parkinson disease; PINK1: PTEN induced kinase 1; POE SHSY5Ys: FLAG-PRKN over-expressing SHSY5Y cells; SDS-PAGE: sodium dodecyl sulfate polyacrylamide gel electrophoresis; TMRM: tetramethylrhodamine methyl ester; WB: western blot; WT: wild-type; ΔΨm: mitochondrial membrane potential